2003
DOI: 10.3748/wjg.v9.i5.1098
|View full text |Cite
|
Sign up to set email alerts
|

A clinical dilemma: abdominal tuberculosis

Abstract: Neither clinical signs, laboratory, radiological and endoscopic methods nor bacteriological and histopathological findings provide a gold standard by themselves in the diagnosis of abdominal TB. However, an algorithm of these diagnostic methods leads to considerably higher precision in the diagnosis of this insidious disease which primarily necessitate a clinical awareness of this serious health problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(163 citation statements)
references
References 13 publications
9
141
0
6
Order By: Relevance
“…Twelve patients presented with obstruction (24%), nine with perforation (18%) and 28 with peritonitis without free air (57%). Intra-operative findings were: frozen abdomen in 10 (20%), bowel perforations in 13 (27), enlarged lymph nodes and ileo-caecal mass in 19 (3%) and obstructed small bowel in seven patients (14%). Eleven patients (22%) had small bowel resection and eight patients (16%) had right hemicolectomies.…”
Section: Group B: Laparotomymentioning
confidence: 99%
“…Twelve patients presented with obstruction (24%), nine with perforation (18%) and 28 with peritonitis without free air (57%). Intra-operative findings were: frozen abdomen in 10 (20%), bowel perforations in 13 (27), enlarged lymph nodes and ileo-caecal mass in 19 (3%) and obstructed small bowel in seven patients (14%). Eleven patients (22%) had small bowel resection and eight patients (16%) had right hemicolectomies.…”
Section: Group B: Laparotomymentioning
confidence: 99%
“…This abdominal form of TB has an insidious course like any other chronic infectious disease without any specific laboratory, radiological or clinical findings. Due to this non-specificity and great difficulties in its diagnosis a number of rapid investigative methods have been surfacing out to aid in the diagnosis of GITB employing a diverse MTB genomic targets including the IS 6110 insertion sequences (16)(17)(18)(19). Undeniably, the PCR systems developed so far have shown good levels of sensitivity (90 to 100%) only on AFB smear -positive samples (20).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with abdominal TB tend to present with abdominal pain, weight loss and fevers [5] [7] [11] [21]- [24]. However, a definitive diagnosis in developing countries with high prevalence of HIV is often a challenge due to but not limited to: low sensitivity and specificity of the clinical symptoms, the paucity of radiological and diagnostic modalities, and difficulties in accessing the affected tissues for a diagnostic specimen [6] [28]. In resource constrained countries, abdominal sonography is traditionally performed very selectively to evaluate specific abnormalities discovered at clinical examination or when the patient has abdominal complaints.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal sonographic findings of TB in patients with advanced immune deficiency include: mesenteric hypo-echoic lymphadenopathy [21] [22] [28]- [31] ascites [21] [26] [27], multiple splenic hypo-echoic nodules and thickened matted bowel loops. Some studies however have found ascites to be more common in HIV negative patients [6] [7] [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation